Pengaruh beban kerja dan persekitaran kerja terhadap tekanan kerja dalam kalangan kakitangan CIMB Bank Berhad di Negeri Kedah dan Perlis - Hushairi, Salleh (2021)
Employees stress is one of the important issues that need to be addressed by every organization and also for researchers in order to understand their impacts on employees and organization. Presently, employees stress is a challenge that many organizations struggle to overcome. Thus, to gain better understanding, this study identifying relationship between workload, working environment towards work stress. The main purpose of this study is to examine relationship between workload and working environment towards work stress among staff of CIMB Bank Berhad in Kedah and Perlis. For data collection, about 165 set of questionnaire was distributed to staff of CIMB Bank Berhad in Kedah and Perlis involving executive, officer and teller. Then, the data were analysed by using IBM SPSS version 26. The result gain through analysis of Pearson correlation and regression indicated that workload has positive relationship towards work stress. However working environtment has negative relationship towards work stress. These finding provides useful information to the management of CIMB Bank Berhad regarding their employees’ well-being and concerning.